Æschere's Head, Grendel's Mother, and the Sword That Isn't a Sword: Unreadable Things in Beowulf. (1st January 2013) - Paz, James
<x xml:space="preserve">Abstract</x> This article engages with thing theory to demonstrate that both Grendel's mother and the giants' sword found in her underwater hall are riddle-like things that resist the kinds of reading that Æschere, a rune-knower and advice-bearer, was meant to provide for King Hrothgar. By killing and decapitating Hrothgar's reader, Grendel's mother highlights an anxiety within Beowulf about 'things' that defy human interpretation and convey monstrous, marginal, or unknowable messages instead. Although Beowulf acknowledges that a wide range of artifacts can be read, the text also reveals that certain enigmatic things exceed their role as readable objects. Liminal things like the giants' sword carry alien stories and histories into the safety of the mead hall, disrupting a longstanding human reliance upon legibility and altering the way that literate communities interpret that which has come before them.